Acculturation as a Type of Intercultural Communication (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is devoted to the study of acculturation as a form of intercultural communication. Theoretical approaches to acculturation, its main stages and mechanisms are considered. The author analyzes the impact of acculturation processes on the individual and society, and identifies the main factors contributing to successful acculturation.